The Pitfall of Selective Environmental Information Disclosure on Stock Price Crash Risk: Evidence From Polluting Listed Companies in China - Xu, Fei; Ji, Qiang; Yang, Mian (Frontiers in Environmental Science, 2021)
The current regulations on environmental information disclosure (EID) of listed companies in China can easily lead to selective disclosure, and this information-hiding disclosure strategy may result in stock price crash risk. In this paper, the EID scores of China’s 1010 polluting listed companies during 2007 and 2017 are first measured by employing text analysis approach. Subsequently, we empirically examine the impacts of corporate’s selective EID on the stock price crash risk. The results indicate that EID of China’s polluting listed companies has significantly increased their stock price crash risk rather than reduced it. Specifically, the EID of polluting companies with lower information efficiency, higher inefficient investment, higher degree of government control, and in lower marketization areas is more likely to increase their stock price crash risk. Additional analyses reveal that selective disclosure of environmental information cannot reduce stock price synchronization and thus cannot reduce the risk of stock price crash.